Complexation between (benzoic acid)(AZO)phenylcalix[4]arene (BPC) with lead and its analytical application. - Lệ, Nguyễn Thị Ngọc; Thụ, Lâm Ngọc; Tám, Lê Văn (Vietnam Journal of Chemistry, 2012)
Lead is a toxic heavy metal that is known to have varied effects on human health. For example, it can adversely affect many organ systems and contribute to numerous conditions such as high blood pressure; anemia, kidney damage, impaired hearing, and mental retardation. Currently, spectrophotometric methods are more often used because of their simplicity and low cost. Although a lot of chromogenic reagents for Pb2+ detection have been reported, none of the reagents was prepared by attaching a chromogenic moiety to a platform of a macrocyclic compound, such as calixarene. It was found that the compound showed the high sensitivity and selectivity toward Pb2+. In basic media, compound shows strong binding ability to Pb2+ ion. Based on the method of continuous variation, calixarene formed a 1:1 complex with Pb2+ ion. Beer’s law is obeyed in the range of 2.0x10-6-2.4x10-5 molL-1 of Pb2+. The apparent molar absorptivity(e) of 1-Pb2+ complex was 1.89 x104 Lmol-1cm-1 at 440 nm, and the detection limit is 1.6x10-6 mol L-1. In this work, a very simple and highly selective method for the determination of lead was developed. The proposed method was applied to the determination of trace amount of Pb2+ in certiﬁed samples.